2011
DOI: 10.1590/s0074-02762011000600017
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of a presumed increase in the biting activity of dengue-virus-infected Aedes aegypti (Diptera: Culicidae) females on virus transmission dynamics

Abstract: Recently, we showed that infection with dengue virus increases the locomotor activity of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…Alternatively, the most cost-effective strategy consisted of six high efficacy adulticide applications per year, reducing the disease burden to the greatest extent and meeting WHO's standard for a cost-effective intervention. Luz et al used a simplified formulation of their model [40] to investigate the potential impact of increased biting rates in dengue infected mosquitoes [42]. The effect of dengue infection on mosquito feeding behavior is not clearly established and different studies yielded controversial results [43], [44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the most cost-effective strategy consisted of six high efficacy adulticide applications per year, reducing the disease burden to the greatest extent and meeting WHO's standard for a cost-effective intervention. Luz et al used a simplified formulation of their model [40] to investigate the potential impact of increased biting rates in dengue infected mosquitoes [42]. The effect of dengue infection on mosquito feeding behavior is not clearly established and different studies yielded controversial results [43], [44].…”
Section: Resultsmentioning
confidence: 99%
“…However, two recent experimental studies support the differential biting rate assumption [45], [46]. Using numerical simulations, Luz et al showed that an increase of 50% of the biting frequency would produce an increase of the numbers of primary and secondary dengue infections of 3.8% and 6.5%, respectively [42]. Another potential vector control strategy, based on the Release of Insects carrying a Dominant Lethal (RIDL) was studied by Atkinson et al [47].…”
Section: Resultsmentioning
confidence: 99%
“…In a simplified mathematical model, if we assume an increase in the biting rate of infected Ae. aegypti , the number of primary and secondary infections also increases ( Luz et al 2011 ). However, the molecular mechanism behind this control has never been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Typical formulations of the equation assume that the biting rate of mosquitoes is unchanged, regardless of infection status. However, the reduction in specific proteins identified in this research, combined with the changes in feeding behavior of DENV-infected mosquitoes seen by others, would indicate that this assumption may be violated in nature and would have consequences for transmission [63,64,67]. Thus, a separate parameter of a INF to account for this alteration in vector biting rate due to infection status is appropriate.…”
Section: Discussionmentioning
confidence: 86%